RESOURCE ESSENCE ANALYSIS IN MANAGEMENT - Silvy Sondari Gadzali; Sonny Santosa; Achmad Choerudin; Ivonne Ayesha; Abu Muna Almaududi Ausat (SEAN Institute, 2023)
If we reflect on the nature of management, we will find confusion of direction in utilising resources. However, people are the crucial resources that management has in achieving goals effectively and efficiently. This research aims to explain the nature of management resources in a straightforward and understandable language. This research includes library research because this research is conducted to search, analyse, interpret and generalise from the facts of the results of thoughts and ideas written by resource management experts. This research is descriptive qualitative with a secondary data analysis approach. This study arrives at the conclusion that to reflect on resource management, a type of work is always carried out which is driven by humans as members of management. This research can be used as a reference for anyone with an interest in discussing HR and management topics. In addition, it can be a material for formal discussion in higher education.